SUGGESTIVE ROLE OF EYE-STALK OF MACROBRACHIUM GANGETICUM BATE, 1868 IN REGULATION OF ITS REPRODUCTIVE BEHAVIOUR. - Gupta, Akhilesh Kumar (Journal of Indian Fisheries Association, 2009)
Role of eye-stalk of Macrobrachium gangeticum Bate, 1868 in its reproductive behaviourhas been examined by conducting deletion and addition experiments. Eye-stalk ablation inducedgonadal maturity in both sexes, leading to change in colour and size of ovaries and increase in GSIand oocyte diameter in females and increased length of testes and diameters of seminiferoustubules in males. Injection of eye-stalk extracts tended to at least partly restrict the effects in bothsexes. The experiments thus suggested that the eye-stalk of M.gangeticum released some gonadinhibiting factors.Key words: Macrobrachium gangeticum, Eye-stalk, Gonads.